Structure and Surface Behavior of Rh Complexes in Ionic Liquids Studied Using Angle-Resolved X-ray Photoelectron Spectroscopy - Hemmeter, Daniel; Paap, Ulrike; Maier, Florian; Steinrück, Hans-Peter (Catalysts, 2023)
We present an ARXPS study on the surface composition and interfacial behavior of commercial [Rh(COD)2][TfO] in [C2C1Im][TfO], [C4C1Im][TfO], [C8C1Im][TfO], and [C2C1Im][EtOSO3]. The complex was found to be non-intact in a solution of these ILs through the loss of COD ligands, accompanied by the depletion of the metal center from the IL/vacuum interface. Increasing the chain length of the aliphatic substituent on the imidazolium cation of the [TfO]−-based ILs led to a more pronounced depletion from the interface, due to the higher surface affinity of the solvent cations with the longer alkyl chains. The loss of COD ligands offered facile in situ ligand substitution with surface-active TPPTS to afford a moderate increase in the surface concentration of Rh. We propose the formation of a Schrock−Osborn-type catalyst [Rh(COD)(TPPTS)2][TfO]. Information on the surface composition and targeted design of the gas/IL interface is highly relevant for applications in IL-based catalytic systems, such as in supported ionic liquid phase (SILP) catalysis.
CRIS-Team Scopus Importer:2023-06-09
Keywords: catalysis; ionic liquids; rhodium catalysts; surface analysis; X-ray photoelectron spectroscopy (XPS)